Pengaruh Literasi Keuangan Dan Financial Technology Terhadap Inklusi Keuangan Mahasiswa UINSU - Salwa, Nisrina; Fadhila Rahma, Tri Inda; Nasution, Juliana (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to determine financial literacy and Financial Technology towards financial inclusion of UINSU students (FEBI Stambuk 2017 Students). This type of research uses a quantitative approach. This study uses 2 independent variables, namely financial literacy and Financial Technology (Fintech) with one dependent variable, namely the financial inclusion of UINSU students (FEBI Stambuk 2017 Students). After a literature review and field, and the preparation of hypotheses data in this study were collected through the distribution of questionnaires to 88 donors as a research salmpel with sampling techniques using likert scale. Data is processed through the SPSS 23.0 program with multiple linear regression analysis techniques. The results of this study can be concluded that 1) Financial Literacy has a significant influence on the financial inclusion of UINSU students (FEBI Stambuk Students 2017). With the value of t calculate financial literacy variables 4.583 > 1.663 and significance of 0.000 > 0.05. 2) Financial Technology has a significant influence on the financial inclusion of UINSU students (FEBI Stambuk Students 2017). With the value of t calculate financial technology variables 3.147 > 1.663 and significance of 0.002 > 0.05. 3) simultaneously, the variables of financial literacy and Financial Technology have a significant influence on the financial inclusion of UINSU students (FEBI Stambuk 2017 Students). With the value of F count > F Table 1.387 > 3.10 and significance at 0.00 < 0.05 means that there is a significant influence of variables X1, X2 and variable Y together.